ANALISIS NIDA’ TENTANG SERUAN DALAM QUR’AN SURAHAN-NISA AYAT 1 TERHADAP UMAT YANG BERTAKWA - Febian, Imelda; Siregar, Anita Putri (SULTAN ADAM: Jurnal Hukum dan Sosial, 2024)
This paper aims to analyze an – nida’ in the an – nisa verse  1 opening which emphasizes the origin of human creation and the importance of family relationships. In this verse, Allah Swt reminds all mankind to fear him, the god who created them from one soul (adam) and created his partner (eve) from the same soul, and bred many men and women from both of them. The method used in this writing is a qualitative method that is a literature study that uses a method by collecting secondary data in the from of jurnal papers, online articles, trusted tafsir and other books. The results of this research analysis show 3 main points, namely in the an – nisa verse 1, an – nida is found in.